Forensically important blow flies chrysomya pinguis, C. Villeneuvi, and lucilia porphyrina (Diptera: Calliphoridae) in a case of human remains in Thailand - Monum T. (2017)
© 2017, Korean Society for Parasitology and Tropical Medicine. This is the first study to report Chrysomya pinguis (Walker) and Lucilia porphyrina (Walker) (Diptera: Calliphori-dae) as forensically important blow fly species from human cadavers in Thailand, in addition to Chrysomya villeneuvi (Pat-ton) already known in Thailand. In 2016, a fully decomposed body of an unknown adult male was discovered in a high mountainous forest during winter in Chiang Mai province. The remains were infested heavily with thousands of blow fly larvae feeding simultaneously on them. Morphological identification of adults reared from the larvae, and molecular analysis based on sequencing of 1,247 bp partial mitochondrial cytochrome c oxidase subunit 1 gene (CO1) of the larvae and puparia, confirmed the above mentioned 3 species. The approving forensic fly evidence by molecular approach was described for the first time in Thailand. Moreover, neighbor-joining phylogenetic analysis of the CO1 was performed to compare the relatedness of the species, thereby affirming the accuracy of identification. As species of entomofauna varies among cases in different geographic and climatic circumstances, C. pinguis and L. porphyrina were added to the list of Thai forensic entomology caseworks, including colonizers of human remains in open, high mountainous areas during winter. Further research should focus on these 3 species, for which no developmental data are currently available.